ANALISIS PERGESERAN KATEGORI PADA FRASA BERPREPOSISI DALAM SEBUAH NOVEL BERJUDUL “UGLY LOVE” - Sunarti Desrieny Tambunan (Asosiasi Dosen Muda Indonesia, 2024)
The purpose of this study is to identify the category shifts employed by the translator in translating prepositional phrases in a novel titled *